2015
DOI: 10.1007/s13593-015-0282-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of crop protection strategies on natural enemies in organic apple production

Abstract: Organic farming is mainly viewed as a homogeneous production system. Organic farming is also commonly thought to favor natural enemies of pests for crop protection. However, organic farming involves very different management practices and, in turn, various protection strategies. There is little knowledge on the influence of protection strategies on natural enemies in organic agriculture. Here, we analyzed crop protection strategies of 24 organic apple farmers in Southeast France. We also analyzed natural enemy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…Based on these combinations, six types of strategies were identified on a rather small sample. This diversity of protection strategies within a common context was also observed by Marliac et al (2015), who identified four types of protection strategies within a sample of 24 organic apple growers in south-east France. However, given the number of interacting drivers involved, each farm studied appeared to be a unique case where these processes took specific values.…”
Section: Apple Protection As Viewed By Farmers: a Range Of Constraintsupporting
confidence: 60%
See 1 more Smart Citation
“…Based on these combinations, six types of strategies were identified on a rather small sample. This diversity of protection strategies within a common context was also observed by Marliac et al (2015), who identified four types of protection strategies within a sample of 24 organic apple growers in south-east France. However, given the number of interacting drivers involved, each farm studied appeared to be a unique case where these processes took specific values.…”
Section: Apple Protection As Viewed By Farmers: a Range Of Constraintsupporting
confidence: 60%
“…It also renders it possible to both aggregate and separate different types of products (Brunet et al, 2008). This indicator has already been used in several studies to compare different orchard production systems (Marliac et al, 2015;Simon et al, 2011;Laget et al, 2014).…”
Section: Analyzing Protection Practices At the Agc Levelmentioning
confidence: 99%
“…the dominant species represents less than 80% of the trees). Some farmers under organic management chose to decrease the frequency of mowing to promote the abundance and diversity of natural enemies within orchards (Marliac et al, 2015). Since the ground cover density did not vary (natural grass species) and was very dense in all the orchards, we only characterised its mean height based on the measurements made at the two spider sampling dates.…”
Section: Characterisation Of the Orchards And Crop Management Practicmentioning
confidence: 99%
“…Commercial organic apple orchards in the South-East of France are a highly sprayed crop with, on average, 25 pesticides applied each year (Sauphanor et al, 2009;Marliac et al, 2015). An additional advantage of orchards is their perennial and multi-strata status (soil surface, grass and trees) in which habitat management is thought to have greater effects (Landis et al, 2000;Simon et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Today, there is general agreement among the public and, growers that crop protection should rely less on the use of synthetic pesticides and more on agro-ecology principles (Jones et al, 2016;Marliac, Penvern, Barbier, Lescourret, & Capowiez, 2015). Among these principles, biological control through the promotion of natural enemies and with limited use of pesticides is of prime importance .…”
Section: Introductionmentioning
confidence: 99%